Collaboration in resource sharing among Malaysian academic libraries in a digital environment - Kaur, Harvinder; Kaur, Kiran; Singh, Diljit (2006)
The need for resource sharing among libraries has become even more important today with constraints of finance, space, and manpower. Traditional forms of resource sharing – inter-library loans and document delivery – are more suited to a print environment than a digital environment. The digital environment however provides many new opportunities for resource sharing, and the literature suggests many emerging models. This paper examines the views, practices, and plans of resource sharing among Malaysian academic libraries. From the interviews conducted, it was noted that librarians were aware of and support the concept of resource sharing. Current resource sharing activities in Malaysia centre on inter-library loans and document delivery services. Resource sharing in the digital environment is based on existing collaborative projects, and the proposed Consortium of Malaysian Libraries. Factors that influence success in resource sharing include the need for a shared commitment, the willingness to contribute, technologically skilled staff, and a need to understand legal implications.